URGENSI PERAN MUI DALAM MENUMBUHKAN KARAKTER ANTI KORUPSI TERHADAP ORMAS KEAGAMAAN - Aminah, Siti; Mahmudah, Siti (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2023)
The purpose of this study was to describe the strategic role of the Indonesian Ulema Council in Kediri City in an effort to foster Anti-corruption character against religious organizations in Kediri City in 2022, what steps are taken by the Indonesian Ulema Council in Kediri City in growing Anti-corruption character against religious organizations in Kediri City in 2022, describe what are the supporting and inhibiting factors of the Indonesian Ulema Council in Kediri City in growing Anti-corruption character against religious organizations in Kediri City in 2022. This research is as a study material, and additional literature of the MUI Kediri work program in fostering character and anti-corruption education in Kediri. The conclusion obtained from this study is from 34 correspondents 35% about 12 people give advice to DPD MUI to provide socialization of MUI Fatwa related to Anti-corruption. 20% about 7 people gave advice to hold anti-corruption Character Education, 15% about 5 people gave advice to DPD MUI Kediri to hold a visit to religious community organizations in Kediri. 12% about 4 people gave suggestions to synergize with other institutions such as the KPK, 9% about 3 people gave suggestions to hold Anti-corruption education seminars 6% about 2 people to hold interactive discussions, 3% about 1 person gave input to be held education and coaching regularly and included in the program of DPD MUI Kediri.